Optimalisasi Pengembangan Soft Skill Melalui Teknologi Artificial Intellegence di Pesantren - Husairi, Husairi; Sodikin, Sodikin (Al-Jadwa: Jurnal Studi Islam, 2023)
The development of Soft Skills in training is an urgent necessity in order to survive under any circumstances. This article aims to explore the process of developing central Soft Skills with the help of artificial intelligence technology. (AI). (AI). This AI help will help teachers and teachers as it can provide maximum guidance to teachers in training facilities that have limited access to information. The results of this study are based on a qualitative approach with a case study approach. The data was obtained through interviews with the centers or teachers involved in the development of these Soft Skills. Data is analyzed through three steps: condensation and display verification. The results of this study show that the use of artificial intelligence (AI) technology has a significant impact on the development of central Soft Skills in training. Implementation of Soft Skills development through artificial intelligence (AI) technology starts with (1) personalized learning, (2) interactive and impressive learning, (3) automated and real-time feedback, (4) collaborative learning, and (5) evaluation and assistance. The integration of artificial intelligence (AI) technology into the learning process will help centers to sharpen practical skills such as communication, leadership, and collaboration in an environment that supports experimentation without great risk. The main challenge faced by trainers in developing Soft Skills through training technology is the old values adopted by the trainers. But all that can be overcome with the maturity of the resources of the trainees.